THE PRESERVATION OF PECULIARITIES OF LEXICAL AND SEMANTIC ASSOCIATION OF TERMINOGIAL PHRASAL COMPONENTSIN IN INDIRECT TRANSLATION - Boboyev Yusuf Beknazarovich (American Journals, 2024)
The article discusses the peculiarities of lexical and semantic association of terminological phrasal components used in Ray Bradbury’s stories in English and Uzbek Languages.
Keywords: Science fiction scientific term, lexco-semantic, phrase, telekinesis telepathy, field, smell, stylistic devices, space